THE CHLOROFORM EXTRACT OF SOURSOP (ANNONA MURICATA LINN) LEAVES AS ANTIBIOTIC TOWARDS PROPIONIBACTERIUM ACNES - Dian Riana Ningsih (Jurnal Penelitian Saintek, 2017)
Propionibacterium acnes (P. acnes) was bacterium commonly found in acne. P. acne was microaerophilic bacterium which can be as a normal fl ora as inhabitants of skin but also is a facultative pathogen. Soursop was a plant that can be used for acne, wounds ulcers, convulsions, and lice cure. This study was aimed to determine the antibacterial activity of soursop leaves against P. acnes bacteria using chloroform solvent. Antibacterial activity test was performed by well diffusion method. The inhibition activity of soursop leaves chloroform extracts was indicated by the appearance of clear zone. The results show that the extract of chloroform at a concentration of 1000, 2000, 3000, and 4000 ppm is able to inhibit the growth of P. acnes bacteria with the inhibition zone of 8.86, 12.12, 12.42, and 15.48 mm respectively. The greater the inhibition zone, the higher the concentrations of n-hexane extract of the soursop leaves.